Moving Out of Poverty : Volume 4. Rising from the Ashes of Conflict - Narayan, Deepa; Petesch, Patti (Washington, DC: World Bank and Palgrave Macmillan, 2012)
Lifting people out of poverty is one of the great challenges facing the international community today. It has become still more daunting in the context of the global financial crisis, which has severe implications for the poorest people in the world. Almost 1.4 billion people in developing countries live in poverty, according to recent estimates by the World Bank, and a significant part of this population lives in chronic poverty. This is the fourth in a series of volumes emerging from the global moving out of poverty study, which explores mobility from the perspectives of poor people who have moved out of poverty in more than 500 communities across 15 countries. The research on conflict-affected countries was managed by the global development network in partnership with the World Bank. This volume examines the social, political, and economic institutions facing poor people in post-conflict environments, where lives have been turned upside down by violence and instability. Based on original evidence from over a hundred communities in seven countries, the study documents the strategies that poor people use to cope with and move out of poverty, and it concludes with important policy recommendations.